'Real men grill vegetables, not dead animals': Discourse representations of men in an online vegan community. (October 2022) - Brookes, Gavin; Chałupnik, Małgorzata
Abstract: This article critically examines discourse representations of men in a large online vegan community. The analysis reveals a set of discourses which provide oppositional representations of vegan and non-vegan men, wherein the former is aligned with hegemonic masculine norms and the latter represented as transgressing or falling short of these norms. We interpret these discourses as providing means for the forum members to resist societal-level discourses which frame veganism and vegan men as feminine or 'unmanly', while also performing a social support function of reassuring posters who express concerns about how their veganism may impact how others perceive them and their masculinity. However, we also argue that such discourses can be considered problematic from an ecofeminist perspective, as they orient to and reinforce a hegemonic gender hierarchy which has enabled, and continues to enable, gender oppression, animal exploitation and the broader destruction of the natural world.